Rhythm, Resonance and Kinaesthetic Enskilment in a Ghanaian Bus Station. Issue 3 (27th May 2017) - Stasik, Michael
ABSTRACT: In this article, I explore the workings of a long-distance bus station in Accra, Ghana, by focusing on the relationship between rhythm and practice. In Accra's station, departures do not follow pre-designated scripts of clock-time but are timed collectively by the inflow of passengers. These inflows follow diverse rhythmic temporalities co-composed in Accra and in the destinations served from the station. I show that by attending to the rhythmicity of activities in the yard, the station dwellers accommodate motional inputs that take shape hundreds of kilometres away. They do so by way of kinaesthetic enskilment, hence a tacit way of attuning to movements and rhythms. This link between rhythmanalysis and the anthropology of the senses, I suggest, offers a useful conceptual gateway for understanding West African practices of road travel.